Predicted high thermoelectric performance in a two-dimensional indium telluride monolayer and its dependence on strain. Issue 44 (1st November 2019) - Li, Min-Shan; Chen, Kai-Xuan; Mo, Dong-Chuan; Lyu, Shu-Shen
Abstract : Group IIIA–VIA monolayers are predicted to exhibit high thermoelectric performance, owing to their low thermal conductance and unique band structures. Abstract : In recent years, another two-dimensional (2D) family, monolayer metal monochalcogenides (group IIIA–VIA), has attracted extensive attention. In this work, we adopt density functional theory (DFT) and the non-equilibrium Green's function (NEGF) method to systematically investigate the ballistic thermoelectric properties of the IIIA–VIA family, including GaS, GaSe, GaTe, InS, InSe, and InTe. Among others, the InTe monolayer possesses the highest figure of merit, ZT = 2.03 at 300 K, due to its ultra-low thermal conductance. Biaxial strain in the range of −10% (compressive) to 10% (tensile) is applied to the InTe monolayer and the strain-induced electronic and thermal transport properties are discussed. The maximum ZT (up to 2.7) for the InTe monolayer at 300 K is achieved under an 8% tensile strain.